The Relationship between Eating Behaviors of Children and Mothers, and Nutritional Status of Children - Aktac, F.E. Gunes, S.; Islamoglu, A.H.; Akduman, G. (International Journal of Child Health and Nutrition, 2020)
Introduction: Parents have a significant impact on child nutrition and the child's eating habits in long-term behavior. This study aims to examine the effects of mothers' attitudes on the eating behaviors of children and the determination of their nutritional status. Method: Children's eating habits and mothers' eating attitudes were examined in 417 children with face-to-face interviews using the Child Feeding Questionnaire (CFQ). The participants' anthropometric characteristics were determined, and body mass indexes (kg/m2) were calculated. AnthroPlus software was used to determine the children’s BMI-for-age Z-scores. BeBiS nutrition information system was used to assess children’s food intake. Results: The mothers' median BMI was above the overweight threshold. The lowest CFQ score was for perceived child weight, and the maximum score was for food restriction. Significant differences were found in mothers ages, mothers' BMIs, children's WAZ and BAZ scores, and BMIs, weight (p<0.001), perceived parent weight scores (p=0.04), and pressure to eat (p=0.04). Families should be conscious about nutrition for the protection and promotion of children's health.